Risk management in developing marketing strategy for organic rice in Kediri Regency [Manajemen risiko dalam pengembangan strategi pemasaran beras organik di Kabupaten Kediri] - Haried, Dio Nanda; Muhaimin, Abdul Wahib; Andriani, Dwi Retno; Yulianti, Nurdiana (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
The current development of marketing has been experiencing growth over time. Every activity carried out by marketing efforts results in impacts or risks. Assessing marketing activity risks allows marketers to control and monitor each risk and ultimately achieve their company's strategies. This research aimed to analyze the marketing risks of organic rice in Kediri Regency and formulate risk mitigation strategies for marketing organic rice in Kediri Regency. Expert respondents in this study were seven individuals selected through a census method who were organic rice marketers in the Kediri Regency. This study used nine marketing risk variables and 22 marketing risk indicators. The methods employed included Fuzzy Failure Mode Effect Analysis (FFMEA) and Analytical Hierarchy Process (AHP). FFMEA aimed to identify risks and provide risk assessments, while AHP aimed to determine alternative strategies for marketing risks. The results of the study showed that the highest priority risk levels and marketing risks included uncertainty in organic rice demand, price competition, limitations in sales areas, consumers' lack of familiarity with the target product, limited knowledge about sustainable technology, sorting practices that did not meet standards, packaging that affected product durability, minimal knowledge related to digital payments, and lack of partnership information. Nine strategies were proposed to minimize the existing risks, namely expanding digital marketing channels, offering product bundles, strengthening sales through cooperation with local stores, creating promotional media, conducting marketing management training, optimizing existing processes, improving packaging quality according to standards, financial planning related to business development, and improving information flow between partnerships.